2014
DOI: 10.1007/s40259-014-0107-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Embedded Pure Xenogenous Bovine Platelet Gel on Experimental Tendon Healing, Modelling and Remodelling

Abstract: Bovine platelet gel-embedded artificial tendon could be considered as a new option in reconstruction and healing of large tendon defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Clinical usage of PRP has been reported to have few significant complications7, which coincides with the finding of the current study. The fact that FD-PRP achieved the similar tendency for trabecular formation and mechanical strength to BMP indicates that FD-PRP achieves accelerated bone formation in the osteoinductive manner as BMP does30. This should be investigated in detail in a future study.…”
Section: Discussionmentioning
confidence: 87%
“…Clinical usage of PRP has been reported to have few significant complications7, which coincides with the finding of the current study. The fact that FD-PRP achieved the similar tendency for trabecular formation and mechanical strength to BMP indicates that FD-PRP achieves accelerated bone formation in the osteoinductive manner as BMP does30. This should be investigated in detail in a future study.…”
Section: Discussionmentioning
confidence: 87%
“…We decalcified turtle bone to expose osteoinductive growth factors from the mineralized matrix, thereby enhancing the bone formation process. There is higher variability in concentration of BMPs among the same DBM (ORYAN et al, 2014b). This variability questions DBM product reliability and, possibly, their efficacy in providing consistent osteoinduction .…”
Section: Discussionmentioning
confidence: 99%
“…DBM is able to function as a graft extender in humans (LIEBSCHNER, 2004). After demineralization, DBM retains much of the proteinaceous components native to bone, with small amounts of calcium-based solids, inorganic phosphates and some trace cell debris (ORYAN et al, 2014b). Previous experimental studies have demonstrated that the implantation of DBM into subcutaneous or muscular sites induces the proliferation of mesenchymal stem cells which differentiate to cartilage cells (MOSHIRI and ORYAN, 2013) and the synthesis of cartilage tissues, and subsequently there is a process similar to endochondral ossification.…”
Section: Discussionmentioning
confidence: 99%
“…42,49,88 Platelet rich plasma (PRP) and its other forms (gel and glue) can be obtained from patients' anticoagulant peripheral blood by one or two step centrifugation. 107,119,[121][122][123] PRPs are different from each other based on their platelet concentration which is 1.5 to 10 times greater than the physiologic plasma. In addition, they are different based on their source (auto-, allo-, and xenograft), and also presence/absence and concentration of white blood cells.…”
Section: Co-administration Of Healing Promotive Factors and Stem Cellmentioning
confidence: 99%
“…In the platelet gel, the platelets release their growth factors before implantation of the graft so that the beneficial effects of platelet gel start to contribute in the healing process at the surgical implantation time. 107,123 Presence of WBCs in PRP may modulate the inflammatory phase of bone healing. The most important growth factor of platelet concentrates is PDGF which is responsible for several osteoinductive and osteoconductive events.…”
Section: Co-administration Of Healing Promotive Factors and Stem Cellmentioning
confidence: 99%